Programming from specifications - Morgan, Carroll (Prentice Hall, 1994)
Providing a thorough treatment of most elementary programme development techniques, this revised edition covers topics such as procedures, parameters, recursion and data refinement, with the integration of specification, development and coding, based on ordinary (classical) logic. This second edition features: substantial restructuring of earlier material, streamlining the introduction of programming language features; simplified presentation of procedures, parameters and recursion; an expanded chapter on data refinement, giving the much simpler laws that specialize to functional abstractions